Natural products for the treatment of allergic rhinitis: focus on cellular signaling pathways and pharmacological targets - Moradi, Shabnam; Khazaei, Hosna; Tarlan, Mitra; Jasemi, Seyed Vahid; Joshi, Tanuj; Aneva, Ina Yosifova; Farzaei, Mohammad Hosein; Echeverría, Javier (Frontiers in Pharmacology, 2024)
Background: Allergic rhinitis is an inflammatory disease dependent on immunoglobulin E and causes inflammation of the nasal mucosa, leading to decreased quality of life for affected patients.Since common treatments, including corticosteroids and antihistamines, have temporary therapeutic effects and numerous side effects, investigating natural compounds effective in improving allergic rhinitis with low complications and high efficacy can be significant and necessary.Purpose: This study aims to present a comprehensive and critical evaluation of the effect of natural compounds in improving allergic rhinitis.Methods: Studies were identified through systematic searches of ScienceDirect, PubMed, Scopus, and Web of Sciences databases. Eligibility checks were conducted based on predefined selection criteria. Forty-six articles were included in this study.Results and Discussion: Phytochemicals, including flavonoids, alkaloids, terpenoids, and other compounds showed significant anti-inflammatory and antihistaminic effects. These compounds alleviate allergic rhinitis symptoms by inhibiting inflammatory mediators, oxidative stress, apoptosis, and key signaling pathways such as MAPK/NFκB and TLR4/MyD88/NF-κB.Conclusions: Phytochemicals exhibit anti-inflammatory and antioxidant properties, making them promising adjuncts in allergic rhinitis treatment. Compared to traditional therapies, natural compounds offer a safer, multi-targeted approach with fewer side effects, improving patient outcomes.